Pengaruh Efect Efficacy Dalam Meningkatkan Kinerja Karyawan - Putri, Adinda; Larasati, Titik; Diani , Virza Ratna; Yahya, Ananda Intan Fadhilah; Merdiaty, Netty (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
Dynamic business challenges encourage organizations to develop new methods to improve productivity, effectiveness, and efficiency. Employee performance, according to responsibilities (Cita LW, 2016), determines organizational success. Optimal performance requires emotional intelligence, intellectual intelligence, commitment, motivation, and job satisfaction. Self-efficacy, an individual's belief in accomplishing a task, is critical. Motivation, influenced by the employee's attitude towards the work situation, is also crucial, with a proactive and positive attitude strengthening motivation for optimal performance. The method used in this research is the literature review method, where data is collected from various publication sources such as books, journals, research articles, and other relevant sources. The results of this literature review research show that Self Efficacy has a significant positive impact on job satisfaction and employee motivation. Self Efficacy helps employees feel appropriate and comfortable in their jobs, set clear goals, put in maximum effort, and persevere in the face of challenges, which overall improves their performance. Although innovation is expected to improve performance, its implementation is still not optimal and innovative features are not fully utilized. Therefore, further support and training is needed so that employees can effectively utilize innovations to maximize organizational performance.